Prevalence of anti-hepatitis E virus antibodies in domestic animal from three representative provinces of Burkina Faso. (June 2019) - Ouoba, Jean Bienvenue; Traore, Kuan Abdoulaye; Rouamba, Hortense; Setondji, Komi Victor-Mari; Minoungou, Germaine L.; Ouoba, Bruno Lalidia; Ouedraogo, Anne; Moctar, Sidi; M'Bengue, Alphonsine Kouassi; Kakou, Solange Ngazoa; Doumbia, Moussa; Traore, Alfred S.; et al.
Abstract: Four major genotypes of Hepatitis E virus (HEV) have been documented worldwide (1–4) with genotypes 1 and 2 found in human in Sub-Saharan Africa. Human Hepatitis cases due to HEV genotype 3 and 4 are zoonotic with various animal identified as possible reservoirs. Recently, HEV genotype 3 was found in pigs and human beings in West Africa, which may change the epidemic in human. Here, we assessed the prevalence of HEV antibodies in various domestic and wild mammalians in Burkina Faso. Random sampling was performed between 2015 and 2017 to collect serum from 100 rabbits (Oryctolagus cuniculus), 19 hares ( Lepus africana ), 72 cattle (Bos taurus), 75 sheep (Ovis aries) and 81 goats (Capra aegagrus) in three provinces in Burkina Faso. A multi-species ELISA was performed on serum samples from 328 domestic animals and 19 hunting hares. HEV total antibodies were identified in 121 out of 347 specimens (34.9% CI95% [29.9–39.9]). Sera from rabbits (60% CI95% [50.4–69.6]), hares (52.6% CI95% [30.2–75.1]), cattle (26.4% CI95% [16.2–36.6]), sheep (12.0% CI95% [4.6–19.4]), and goats (28.4% CI95% [18.6–38.2]) tested positive for antibodies anti-HEV. In this study we evidence presence of HEV antibodies in various mammalians and highlight the importance of these species in the epidemiology of HEV infection in Burkina Faso.